2006
DOI: 10.1002/cne.21040
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic input to OFF parasol ganglion cells in macaque retina

Abstract: A Neurobiotin-injected OFF parasol cell from midperipheral macaque retina was studied by reconstruction of serial ultrathin sections and compared with ON parasol cells studied previously. In most respects, the synaptic inputs to the two subtypes were similar. Only a few of the amacrine cell processes that provided input to the labeled OFF parasol ganglion cell dendrites made or received inputs within the series, and none of these interactions were with the bipolar cells or other amacrine cells presynaptic to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 56 publications
(62 reference statements)
4
37
0
Order By: Relevance
“…Together with our findings indicating that WNT7B was localized to retinal ganglion cells and that its expression was significantly upregulated in experimental myopic eyes, these data support the hypothesis that WNT7B and GJD2 co-operatively regulate the normal growth of the eye through interactions between the alpha-ganglion cells and AII amacrine cells. Interestingly, alpha-ganglion cells are predominantly observed in the peripheral retina and have large dendritic regions to receive inputs from amacrine cells 47,[53][54][55][56][57] . The hypothesis that alpha- ganglion cells and AII amacrine cells are implicated in emmetropization is consistent with the peripheral defocus theory, a theory of myopia development that has been supported by clinical evidence [58][59][60][61] .…”
Section: Discussionmentioning
confidence: 99%
“…Together with our findings indicating that WNT7B was localized to retinal ganglion cells and that its expression was significantly upregulated in experimental myopic eyes, these data support the hypothesis that WNT7B and GJD2 co-operatively regulate the normal growth of the eye through interactions between the alpha-ganglion cells and AII amacrine cells. Interestingly, alpha-ganglion cells are predominantly observed in the peripheral retina and have large dendritic regions to receive inputs from amacrine cells 47,[53][54][55][56][57] . The hypothesis that alpha- ganglion cells and AII amacrine cells are implicated in emmetropization is consistent with the peripheral defocus theory, a theory of myopia development that has been supported by clinical evidence [58][59][60][61] .…”
Section: Discussionmentioning
confidence: 99%
“…The semi-loose seal NB electroporation method differs from previously described juxtacellular labeling methods [10][11][12][13][14] in five significant respects. filling of the same cell was relatively poor by comparison and was accompanied by substantial dye leakage at the somal recording site, even though subsequent PSP recordings showed that the DSGC was functioning normally.…”
Section: Semi-loose Seal Neurobiotin Electroporation For Recording Anmentioning
confidence: 98%
“…Electroporation [8,9] and juxtacellular labeling methods [10][11][12][13][14] have been developed to insert genes, fluorescent indicators, peptides, and dyes, either into the extracellular space with larger electrodes or by targeting single cells with smaller electrodes. The juxtacellular method employs medium-to high-impedance electrodes for extracellular spike recording, and the large-amplitude pulses (10-20 V or 5-50 nA for up to 25 min) can lead to cellular damage and/ or dye spillover.…”
Section: Introductionmentioning
confidence: 99%
“…The limited role of OFF-bipolars is also suggested by the large difference in the degree of transiency between the (LϩM)-OFF responses of SBCs and OFF-parasol cells. Specifically, the degree of transiency of RGC responses is thought to be established largely at the synapse between cones and bipolars (Awatramani and Slaughter, 2000;DeVries, 2000;DeVries et al, 2006), yet the DB2 and DB3 OFF-bipolar cells that provide input to OFF-parasol cells are the only OFF-bipolar cells appropriately positioned to provide input to SBCs (Calkins et al, 1998;Jacoby et al, 2000;Bordt et al, 2006). Thus, a large role for OFF-bipolars would seem to imply a more similar degree of transiency in SBCs and OFF-parasol cells than was observed.…”
Section: Circuitry For Chromatic and Spatial Opponencymentioning
confidence: 99%